TCP-friendly streaming medium transmitting mechanism in wireless network - CHEN Zhi-gang; DENG Xiao-heng; ZHANG Lian-ming; ZHAO Ming (Tongxin xuebao)
To maintain Streaming media services flows friendly to TCP flows and h/ld the QoS of the streaming service in wireless networks,an adaptive rate control mechanism was proposed.Packet loss between.etwork congestion and wireless link error was distinguished to ’et the accurate state of the networks by the receiver.Occupati/n of the receiver buffer,which reflected how long the temporar)ly stored streaming medium data could be played,was also combined into this algorithm.And tradeoff between TCP-friendly and QoS of streaming media service was achieved through multi-level rate adjustment according to packet loss rate of congestion and queue length of receiver.The results of simulations show that good throughput was gained compared with TCP and TFRC,at most reaching 2M,in condition of 0-0.1 link drop rate,2 and 32 conncections.As link error and congestion was seperated by WTFCC,therefor,end to end packet drop rate was higher than TCP and TFRC,and also of higer throughput.Nomalized throughput indicated that WTFCC was friendly to TCP.